2014
DOI: 10.1021/ol503132r
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Ring Closure and Metal Triggered Ring Opening: Syntheses of Macrocyclic and Linear Hexapyrroles

Abstract: A C6F5-substituted hexapyrrane (1) was synthesized in one step. Oxidative cyclization of 1 with DDQ afforded a phlorin-dipyrrin conjugate (2), and subsequent FeCl3-assisted oxidative cleavage of 2 afforded a terminally di-α-methoxy substituted hexapyrrin (3). On the other hand, oxidation of 1 with FeCl3 afforded 3, a hexapyrrinone Fe(3+) complex (4), and a hexaphyrin (1,1,1,1,1,0) (5). These results indicate that the oxidation of hexapyrranes may be developed as an effective approach for the syntheses of novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The coordination compound 9 Pd of a hexapyrrolic ligand was structurally characterized for the first time by Bröring and co‐workers (Scheme ) . Monometallic helical complexes, such as 10 Fe and 11 Co, were also prepared by oxidative metallation of the precursor ligands . As for bimetallic helicates, we have prepared the bisPd II complex 1 a Pd and the bisNi II complex 2 Ni of partially π‐conjugated hexapyrrolic ligands ,.…”
Section: Introductionmentioning
confidence: 99%
“…The coordination compound 9 Pd of a hexapyrrolic ligand was structurally characterized for the first time by Bröring and co‐workers (Scheme ) . Monometallic helical complexes, such as 10 Fe and 11 Co, were also prepared by oxidative metallation of the precursor ligands . As for bimetallic helicates, we have prepared the bisPd II complex 1 a Pd and the bisNi II complex 2 Ni of partially π‐conjugated hexapyrrolic ligands ,.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the syntheses are outlined in Scheme . The key precursor, P 8 , was synthesized by acid-catalyzed condensation of the corresponding hexapyrrane with N -triisopropylsilyl β-pyrrole carbinol, followed by deprotection with tetra- n -butylammonium fluoride . Then, octapyrrane P 8 was oxidized with 5.5 equiv of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) to afford the neo-confused octaphyrin 1 in a 31% yield.…”
mentioning
confidence: 99%
“…Compound 171 is regarded as a coronene-fused cyclo [6]pyrrole that has a 24 π-electron periphery with an additional 18 π-electron hexaaminobenzene subunit inside the macroring. While 171 showed only very weak absorptions in the region longer than 500 nm, the two-electron-oxidized dicationic form [171] 2+ showed an intense absorption band at 739 nm with a broad band centered at 1150 nm. Reversible oxidation−reduction transformation of 171 using (NO)SbCl 6 and Bu 4 NI was done, and X-ray crystallography highlighted the structural features of 171 and [171] 2+ (Figure 10).…”
Section: Cyclo[6]pyrroles and Analoguesmentioning
confidence: 97%
“…In contrast to 218b with mesomesityl groups, the 1 H NMR data of 218d with meso-m-xylyl groups indicated the presence of trans-2,2′-bipyrrole units and cis-2,2′-bithiophene units. Rath and co-workers 169 Xie and co-workers 171 reported that hexapyrrane 222 was prepared in 13% yield by a condensation reaction with an aldehyde/pyrrole ratio of 1/3, and it was subjected to the oxidative coupling reaction with FeCl 3 to give the same compound 221 in 65% yield. The pyrrole-inverted structure of the normal meso-hexaaryl [26]hexaphyrin(1.1.1.1.1.1) 220 was originally reported by Cavaleiro and co-workers.…”
Section: Expanded Porphyrins Formed By Oxidative Couplingmentioning
confidence: 99%